Procalcitonin is a Predictor of Bacterial Inflammation in Severe Pneumonia In Children (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Severe pneumonia is pneumonia characterized by severe respiratory failure, signs of sepsis and multiple organ dysfunction. Today, the problem of severe pneumonia is relevant, due to the high mortality of the disease, the presence of a wide range of poly and multi-resistant strains of microorganisms. Thus, at present, the issues of studying severe pneumonia in children have not been sufficiently addressed, and the issue of using modern methods of preventing infection remains insufficiently addressed. Issues related to establishing the degree of influence of modifiable and non-modifiable factors on the development and course of severe pneumonia in children require further study; it is necessary to search for new methods for predicting the course and outcome, develop and implement new methods of treating and preventing the disease. In this connection, determining the level of procalcitonin in the blood today is very indicative for diagnosing severe forms of pneumonia.